(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores a new approach to assessing the speech competencies of students with cochlear implants – a 100-point dynamic monitoring system. The author analyzes the acoustic, lexical, grammatical and communicative aspects of speech using digital indicators and substantiates the effectiveness of the rehabilitation process. The results of the study show that the 100-point system provides high results in identifying “weak points” in the student’s speech development and individual planning of corrective work.